Mapping the research landscape of the interactions between obesity and five major complications of diabetes: a bibliometric analysis using knowledge graph visualization - Liu, Yutong; Wang, Yan; Tian, Xiaoming; Jiang, Tianyu; Tang, Chen; Zhu, Likun; Cui, Wenze; Song, Wenhuan; Ma, Chong; Song, Shoujun; Yu, Mingkun (Frontiers in Endocrinology, 2025)
BackgroundObesity significantly increases the risk of major complications of diabetes, including diabetic kidney disease (DKD), diabetic angiopathy, diabetic peripheral neuropathy, diabetic retinopathy, and diabetic foot ulcers (DFU). Although there is a well-established link between obesity and these complications, a comprehensive bibliometric study is needed to map the research landscape and identify the intellectual structure regarding the interactions between obesity and these complications.PurposeThis study aimed to systematically map the global research trends, key themes, and emerging frontiers in the interactions between obesity and five major complications of diabetes using bibliometric analysis and knowledge graph visualization.MethodsA comprehensive bibliometric analysis was conducted via Web of Science, Scopus, and PubMed databases (January 1, 2015, to March 17, 2025) addressing the interplay between obesity and five major complications of diabetes. Using VOSviewer and CiteSpace, the field’s intellectual structure, collaboration networks, and thematic evolution were mapped by analyzing co-citation, keyword co-occurrence, and keyword bursts.ResultsThe analysis of 5,475 articles revealed a rapidly growing field, dominated by research on DKD (n=1,571) and diabetic angiopathy (n=1,303), and led by institutions in the USA and China. Thematic network analysis revealed that ‘obesity’, ‘insulin resistance’, and ‘inflammation’ represent the core pathophysiological mechanisms linking all five complications of diabetes. The keyword burst indicated a significant thematic evolution in the field. Specifically, the focus of studies has transitioned from initial studies on foundational associations to more in-depth studies targeting specific molecular pathways (e.g., ‘NF-kappa B’), high-impact therapeutic interventions (‘metabolic surgery’), and distinct patient populations (‘children’). Through co-citation analysis, we found that research on obesity provides a unified intellectual backbone that structurally integrates the disparate research streams of the five major complications of diabetes.ConclusionThis study quantitatively confirmed that obesity is a scientific nexus for the five major complications of diabetes, shaping a research field characterized by rapid evolution and increasing mechanistic complexity. In conclusion, our findings advocate for a clinical paradigm that establishes weight management as a core component of diabetes treatment, while also guiding future studies toward the systematic clinical translation of mechanism-based interventions.